Internal anal sphincter injury in the immediate postpartum period; Prevalence, risk factors and diagnostic methods in the Swedish perineal laceration registry. (February 2020) - Pihl, Sofia; Blomberg, Marie; Uustal, Eva
Abstract: Risk factors for obstetric external anal sphincter injury are well known. Maternal and obstetric risk factors for internal anal sphincter injury are not extensively studied. The rationale of this study was to evaluate the proportion of internal anal sphincter injury in women with external anal sphincter injury, diagnosed immediately after delivery. This study will assess whether there are additional risks for obstetric internal anal sphincter injury. Objectives: The primary aim was to assess the proportion of internal anal sphincter injury immediately in women with an external sphincter injury and to evaluate maternal and obstetric risk factors for internal anal sphincter injury in women with an external anal sphincter injury only. A secondary aim was to relate the diagnostic methods used for obstetric perineal lacerations to the presence of an internal anal sphincter injury. Study Design: A registry study with data from the Swedish Perineal Laceration Registry 2014–2018. From the registry, the maternal and obstetric characteristics of 3, 333 primiparous women with isolated external (N = 2, 236) versus both external and internal (N = 1, 097) anal sphincter injuries were studied, as were the methods used for examining the obstetric anal sphincter injuries. Results: In 32.9 % (1, 097/3, 333) of primiparous women with an external anal sphincter injury, an internal anal sphincter injury was diagnosed immediately after delivery. A perineal palpatory thickness of less than 10 mm was a diagnostic sign for internal sphincter injury. Well-known risk factors associated with obstetric anal sphincter injuries could not be confirmed as independent risk factors for internal sphincter injury. When the infant is born with an arm beside the head, there is an almost two-fold increased risk for internal sphincter injury. Conclusions: Our main finding is that 32.9 % of women with external anal sphincter injury also have an internal anal sphincter injury. A palpable perineal thickness of less than 10 mm, a degree 4-laceration and an infant born with a hand by the head increases the risk of internal sphincter injury and should be a clinical warning sign.